High Healthcare Utilization in Adolescents with Sickle Cell Disease Prior to Transition to Adult Care: A Retrospective Study - Julie Kanter; Menaka Bhor; Xin Li; Frank Li; Jincy Paulose (Journal of Health Economics and Outcomes Research, 2019)
# Background The transition from pediatric to adult care in the US is often difficult for individuals with sickle cell disease (SCD). Young adults (18 to 25 years of age) have higher acute care utilization and an increased risk of poor outcomes. The current study was designed to provide greater insights into patients (16 to 18 years of age) with SCD prior to their transition to adult care.